Stability analysis of a general nonlinear car-following model. Issue 6 (2nd June 2020) - Du, Wenju; Li, Yinzhen; Zhang, Jiangang; Yu, Jianning
ABSTRACT: In order to study the traffic jams and congestion, this paper investigated the stability of a car-following model on the basis of synchronisation theory of complex network. By using the Lyapunov stability theory and designing the appropriate controller, the car-following model is quickly stabilised and the stability condition of the model is obtained. In addition, the stability of car-following model is studied when the vehicle is subjected to external stochastic disturbance. Finally, the numerical simulation is carried out by using the MATLAB simulation technology, and the results show that the car-following model is rapidly stabilising, and congestion phenomenon is effectively alleviated under the controller designed.